Peran Reserse Kriminal Umum Sebagai Penyelidik Dalam Tindak Pidana Curat Dan Curas (Studi Di Polrestabes Medan) - Hardiyanto, Hardiyanto; Marlina, Marlina; Muazzul, Muazzul (Universitas Medan Area, 2020)
This article discusses the problems regarding the factors causing the increase in criminal by theft robbery in Medan, what is the role of the General Criminal Agency of the Polerstabes Medan and what are the barriers Sin dealing with theft and robbery in the city of Medan. This study uses normative juridical legal research methods, with qualitative analysis. The data used are secondary data using primary legal sources. The results obtained in this study are that the cause of the increase in the level of criminal acts of theft and robbery is internal and external factors of the perpetrators of crime. General Criminal Agency Polrestabes Medan has a role as an investigator and investigator in criminal acts of theft and robbery that can use the authority given by the Criminal Procedure Code and police law. Obstacles obtained by criminal investigators can be categorized as barriers to juridical and non-juridical servitude.